Perioperative Exercise Intention and Influencing Factors: A Multi-Centered Cross-Sectional Study - Lv, Feng; Zhang, Yuxi; Min, Su; Li, Ping; Peng, Lihua; Ren, Li; Yu, Jian; Wang, Bin; Shen, Yiwei; Tong, Shanshan; Jin, Juying; Luo, Xi; et al. (Frontiers in Public Health, 2021)
Abstract Objectives: This study aimed to evaluate the level and factors affecting the perioperative exercise intention in China. Design: This study was a cross-sectional survey in Southwest China. Methods: 499 participants were randomly sampled in eight medical centers from November 23, 2020 to November 27, 2020. The survey included sociodemographic information and a 24-item modified questionnaire, which aimed to evaluate the attitude towards daily exercise, perception of perioperative exercise, social support and the perioperative exercise intention. A multivariable linear regression model was used to evaluate the effect of different items on the patients’ intention for perioperative exercise. Results: A total of 523 responses(95.09%) were collected and 499 (95.41%) were analyzed. The level of exercise intention of the patients during the perioperative period was: 14.83% planned to exercise every day in the hospital, 21.04% planned to exercise every other day, and 35.87% planned to exercise every week. Intensity of daily exercise (P=0.016), positive attitude of daily exercise(P＜0.001), positive attitude of perioperative exercise(P＜0.001) and social support(P＜0.001) were positively associated with the intention for perioperative exercise. Female (P=0.012), non-tertiary center(P=0.011) and preoperative anxiety(P=0.023) was negatively associated with it. Conclusions: The intention for perioperative exercise was low in Southwest China. The authors aimed to relieve preoperative anxiety, promote the education of perioperative exercise, design perioperative exercise programs and provide more social support from medical staff and family for inpatients undergoing elective surgery.